Motivasi Penderita yang Kehilangan Gigi terhadap Penggunaan Gigi Tiruan - Rumambi, Brigita B.; Wowor, Vonny N. S.; Siagian, Krista V. (Universitas Sam Ratulangi, 2021)
Abstract: Denture wearing in society is influenced by several factors, one of which is motivation that can influences the mindset of individuals in decision making. This study was aimed to obtain the description of motivation among denture wearers. This was a literature review study using content analysis. There were four literatures on related topics obtained from the Google Scholar database, PubMed, and Garba Rujukan Digital. The results showed that in general, the external motivation of denture wearers was categorized as moderate, consisted of family support, environment, media, and health facilities. Meanwhile, the internal motivation was categorized as high, consisted of self-perception, interest, need, and expectation. In conclusion, motivations of patients with tooth loss to wear dentures consisted of extrinsic motivation which included the environment, information media, and health facilities, and the intrinsic motivation which included knowledge, self-perception, needs, interests, and expectation.Keywords: motivation; denture wearersÂ Â Abstrak: Penggunaan gigi tiruan pada masyarakat dipengaruhi oleh beberapa faktor salah satunya ialah motivasi yang dapat memengaruhi pola pikir individu dalam pengambilan keputusan. Penelitian ini bertujuan untuk mendapatkan gambaran motivasi penggunaan gigi tiruan. Jenis penelitian ialah studi pustaka dengan menggunakan content analysis. Terdapat empat pustaka mengenai topik terkait, diperoleh dari database Google scholar, PubMed, dan Garba Rujukan Digital. Hasil penelitian mendapatkan motivasi ekstrinsik penderita yang kehilangan gigi dengan penggunaan gigi tiruan umumnya tergolong sedang meliputi dukungan keluarga, lingkungan, media, dan fasilitas kesehatan sedangkan motivasi internal tergolong tinggi meliputi persepsi diri, minat, kebutuhan, dan harapan. Simpulan penelitian ini ialah motivasi penderita yang kehilangan gigi terhadap penggunaan gigi tiruan terdiri dari motivasi motivasi ekstrinsik yang meliputi lingkungan, media informasi dan fasilitas kesehatan dan motivasi intrinsik yang meliputi pengetahuan, persepsi diri, kebutuhan, minat, dan harapan.Kata kunci: motivasi; pengguna gigi tiruan